Determination of dynamic forces in the metal structure of a tower crane based on the multi-mass model - Kovalenko, Valentyn; Kovalenko, Oleg; Stryzhak, Vsevolod; Stryzhak, Mariana; Ruzmetov, Andrew (National Institute of Research and Development in Mechatronics and Measurement Technique, 2023)
The article firstly reviews the current level of research on the dynamics of tower cranes. The publications covering research on the dynamics of crane systems and issues related to sway and trajectory of a load on a flexible suspension are considered. Taking into account the actual characteristics of the drive in dynamic models of tower cranes remains an urgent issue and is the aim of this study To achieve this goal, a multi-mass dynamic model of a tower crane with a slewing tower was obtained, where the drive of the slewing mechanism is taken into account as a separate mass. This approach is the main scientific novelty of this article and enables determination of the forces in elastic connections and other dynamic and kinematic characteristics of the movement depending on changes in the control parameter of the slewing mechanism motor. At the same time, it is possible to take into account the change in torque through the equation of mechanical characteristics, which allows to additionally take into account the influence of internal processes in the drive. When writing the system of equations describing this system, the Lagrange equations of the second kind were used. The resulting mathematical model takes into account the inertial (moments of inertia, reduced masses), elastic and damping characteristics of the structure. The complex movement of the load in both planes is considered. A numerical calculation is performed based on the parameters of a real crane. The change in the drive control parameter during the working cycle is modelled according to different laws.
Keywords: tower crane; slewing mechanism; dynamics